Revisiting pars plana vitrectomy in the primary treatment of diabetic macular edema in the era of pharmacological treatment - Flikier, Stephanie (Taiwan J Ophthalmol, 2019)
Diabetic macular edema (DME) is the most common cause of moderate visual loss in diabetic patients. The current treatment of choice for center-involved DME is anti-vascular endothelial growth factor (VEGF) treatment. Most patients that undergo pharmacological inhibition with anti-VEGF agents need multiple monitoring visits that include optical coherence tomography imaging and multiple injections. Despite this intensive treatment, up to 60% of eyes will have persistent DME after six consecutive monthly injections of an anti-VEGF. Its sustainability over the long term has been questioned. Pars plana vitrectomy (PPV) by increasing the vitreous cavity oxygenation, relieving vitreomacular traction, and removing cytokines from the vitreous cavity may cause long-term resolution of DME without the aforementioned concerns in selected cases. Eyes with vitreomacular traction clearly benefit from PPV as the primary treatment. The role of PPV for eyes with DME without tractional elements is less clear and needs to be explored further.